2012
DOI: 10.5539/ijbm.v7n24p52
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Multi-Criteria Decision Making Model for PESTEL Analysis

Abstract: Although the conceptual structure and nature of PESTEL (Political, Economic, Socio-cultural, Technological, Environment and Legal) analysis requires an integrated approach to analysis, the technical framework of PESTEL does not adequately support such an approach. PESTEL analysis, as it stands, mainly provides a general idea about the macro environmental conditions and situation of a company. This study presents a model to address problems encountered in the measurement and evaluation process of PESTEL analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
130
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(146 citation statements)
references
References 19 publications
1
130
0
15
Order By: Relevance
“…Bununla birlikte, bir eğitim sistemini oluşturan faktörlerin performans düzeyinin ayrıntılı olarak görülebilmesi, karar vericilerin eylem ve davranışlarının yönünü belirlemesi bakımından önemli olan bir diğer konudur. Bir sistemin işleyişine yönelik değerlendirmeler için gerekli olan bu yaklaşım biçimi esasında literatürde bütüncül çerçevede problemleri konu edinen [10,26,27] çalışmalar bulunmakla birlikte bir eğitim sisteminin performansının belirlenmesi ilk kez çalışma konusu edilmiştir. …”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Bununla birlikte, bir eğitim sistemini oluşturan faktörlerin performans düzeyinin ayrıntılı olarak görülebilmesi, karar vericilerin eylem ve davranışlarının yönünü belirlemesi bakımından önemli olan bir diğer konudur. Bir sistemin işleyişine yönelik değerlendirmeler için gerekli olan bu yaklaşım biçimi esasında literatürde bütüncül çerçevede problemleri konu edinen [10,26,27] çalışmalar bulunmakla birlikte bir eğitim sisteminin performansının belirlenmesi ilk kez çalışma konusu edilmiştir. …”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Work streams comprise: a systematic review of the published and grey literature of identified policies and guidelines across the EU for promoting appropriate polypharmacy in older people; case studies of the management of polypharmacy in the consortium countries; a benchmarking survey, aiming to collect quantitative and qualitative data from across the EU to provide a picture of progress towards addressing the urgent challenges associated with polypharmacy; a Political, Economic, Sociocultural, Technological, Environmental and Legal (PESTEL) analysis [23] and analysis of the Strengths, Weaknesses, Opportunities and Threats (SWOT) relating to polypharmacy and adherence management in the consortium countries; and, validation of SIMPATHY findings through an EU-wide consensus (modified Delphi) study.…”
Section: Simpathy Aim and Work Programmementioning
confidence: 99%
“…Para lidar com o cenário encontrado de rivalidade alta e elaborar um plano de ação é necessário, primeiro, se posicionar dentro do quadro da indústria e, depois verificar se o plano de ação envolverá a realização de alterações internas na organização para alterar o posicionamento atual, modificando o cenário da indústria ou, estimulando uma mudança da indústria em si a partir de investimentos em inovações, entre outras iniciativas possíveis (Porter, 1979 (Yüksel, 2012).…”
Section: Ameaça De Substitutosunclassified
“…O ambiente setorial é onde a empresa fornece inputs, vende seus produtos e serviços produzidos para seus consumidores e no qual, também, compete com rivais que produzem produtos similares. Do outro lado, o ambiente macro de uma empresa consiste dos fatores políticos, econômicos, socioculturais, tecnológicos, ecológicos e legais que diretamente ou indiretamente afetam as operações da empresa (Yüksel, 2012).…”
Section: Ameaça De Substitutosunclassified
See 1 more Smart Citation